2008
DOI: 10.1901/jaba.2008.41-405
|View full text |Cite
|
Sign up to set email alerts
|

A Social Stories™ Intervention Package for Students With Autism in Inclusive Classroom Settings

Abstract: A Social Stories TM intervention package was used to teach 2 students with autism to read Social Stories, answer comprehension questions, and engage in role plays. Appropriate social behaviors increased and inappropriate behaviors decreased for both participants, and the effects were maintained for up to 10 months. This intervention package appears to be useful in inclusive classroom environments and does not require intensive supervision of the child's behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 11 publications
1
58
0
8
Order By: Relevance
“…Outcome measures included initiations (n = 2; 67 %), responses (n = 1; 33 %), and interactions (n = 2; 67 %). In two studies, the intervention occurred in a separate classroom setting prior to (i.e., at the start of the school day; or immediately before) the activity (e.g., circle time, centers, play) during which the child was expected to engage in the target behavior (Apple et al 2005;Chan and O'Reilly 2008). In the 3rd study, intervention occurred in the classroom just before unstructured play times (Sansosti and Powell-Smith 2008).…”
Section: Combined Child-specific Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome measures included initiations (n = 2; 67 %), responses (n = 1; 33 %), and interactions (n = 2; 67 %). In two studies, the intervention occurred in a separate classroom setting prior to (i.e., at the start of the school day; or immediately before) the activity (e.g., circle time, centers, play) during which the child was expected to engage in the target behavior (Apple et al 2005;Chan and O'Reilly 2008). In the 3rd study, intervention occurred in the classroom just before unstructured play times (Sansosti and Powell-Smith 2008).…”
Section: Combined Child-specific Studiesmentioning
confidence: 99%
“…In the 3rd study, intervention occurred in the classroom just before unstructured play times (Sansosti and Powell-Smith 2008). Chan and O'Reilly (2008) developed an intervention package combining social stories with adult-mediated instruction. Created social stories followed Gray's (2000) guidelines, and the researcher read the story at the start of the school day (1-4 days a week).…”
Section: Combined Child-specific Studiesmentioning
confidence: 99%
“…Six of these were excluded on the abstract level for the following reasons: one dealt only with task analysis for teaching menstrual care (Klett & Turan, 2012); one dealt with preschoolers with autism enrolled in full-inclusion kindergarten classrooms (Chan & O'Reilly, 2008); one dealt with children between three and four years of age who had specific language impairments (Pettigrew, 1998); one dealt with individuals with learning disabilities (Kalyva & Agaloitis, 2008); one only dealt with changing problematic lunchtime behaviour related to independently entering the dining-room hall (Toplis & Hadwin, 2006); and one with decreasing disruptive behaviour of children with autism (Ozdemir, 2008). The remaining eight papers were read at full-text level and are summarised in Table 1.…”
Section: Phasementioning
confidence: 99%
“…The technique were introduced by Gray (1995) which consists three steps, (1) story reading, (2) comprehension and (3) role playing. A study was conducted by Chan and O'Reilly (2008) has proven that this technique has successfully changed the behaviors of two autistics students under an inclusive classroom without the presence of their counselor during the class in session. Another study by Shari, Brenda & Judith (1998) found out that social stories technique were able to reduce the tantrum behavior of an autistic student.…”
mentioning
confidence: 99%
“…According to Chan and O'Reilly (2008), a social story is one of the effective ways to work on a particular understanding of autistic children whom are facing problems with communication and thus changing their behavior and promote effective teaching and learning.…”
mentioning
confidence: 99%